ENHANCEMENT OF TOMATO GROWTH AND BIOCONTROL OF FUSARIUM SOLANI ROOT ROT DISEASE BY STREPTOMYCES ROCHEI BT02 - Phong V. Nguyen; Hảo Vĩnh Lưu Nguyễn; Đạm T. Lê; Hạnh H. T. Nguyễn (SEAMEO BIOTROP, 2024)
This study investigated the dual role of Streptomyces rochei BT02 in promoting tomato growth and suppressing Fusarium solani, the causative agent of tomato root rot disease. Various assays were conducted to evaluate the plant growth-promoting attributes of strain BT02 including indole-3-acetic acid (IAA) biosynthesis, phosphate solubilization, biofilm formation, and siderophore production. Under in vitro conditions, strain BT02 exhibited plant growth-promoting characteristics such as cellulose degradation, phosphate solubilization, IAA synthesis, biofilm formation, and siderophore production. Application of strain BT02 significantly improved tomato seed germination (26.7%), with enhanced sprout and radicle lengths and seed vigor (38.6%). Greenhouse experiments revealed substantial increases in plant height, leaf and branch numbers, inflorescence, and flower number, emphasizing the positive impact of strain BT02 on overall plant growth. The BT02 strain demonstrated antagonistic efficacy of 45.3 to 58.9% against Fusarium solani, as evidenced by the dual culture and agar well diffusion methods. Under greenhouse conditions, strain BT02 significantly reduced disease incidence and demonstrated control efficacy of 41.6% against Fusarium solani, highlighting its biocontrol potential. This study provides insights into the mechanisms employed by Streptomyces rochei BT02 to enhance plant growth and suppress root rot disease, paving the way for its application as a biocontrol agent in sustainable agriculture.